Allium victorialis L. Extracts Promote Activity of FXR to Ameliorate Alcoholic Liver Disease: Targeting Liver Lipid Deposition and Inflammation - Cui, Zhen-Yu; Han, Xin; Jiang, Yu-Chen; Dou, Jia-Yi; Yao, Kun-Chen; Hu, Zhong-He; Yuan, Ming-Hui; Bao, Xiao-Xue; Zhou, Mei-Jie; Liu, Yue; Lian, Li-Hua; Zhang, Xian; et al. (Frontiers in Pharmacology, 2021)
Allium victorialis L. (AVL) is a traditionally medicine recorded in Compendium of Materia Medica (the Ming Dynasty). General, it’s used for hemostasis, analgesia, antiinflammation, anti-oxidation, especially facilitate the hepatoprotective effect. In recent years, it has received more and more attention due to its special nutritional and medicinal value. The present study investigates the effect and potential mechanism of AVL against alcoholic liver disease (ALD). C57BL/6 mice were fed with Lieber-DeCarli diet containing 5% ethanol plus a single ethanol gavage (5g/kg), following with AVL or silymarin administrated. AML12 cells were stimulated with ethanol and incubated with AVL. AVL significantly reduced serum transaminase, liver TG, and attenuated histopathological changes caused by ethanol. AVL significantly inhibited SREBP1 and its target genes, regulated lipin1/2, increased the PPARα and its target genes, and decreased PPARγ expression caused by ethanol. In addition, AVL significantly enhanced FXR, LXRs, Sirt1, and AMPK expressions compared with EtOH group. AVL also inhibited inflammatory factors, NLRP3, and F4/80 and MPO, macrophage and neutrophil markers. In vitro, AVL significantly reduced lipid droplets, lipid metabolism enzymes, and inflammatory factors depending on FXR activation. AVL could ameliorate alcoholic steatohepatitis, lipid deposition and inflammation in ALD by targeting FXR activation.